Echoes of silence: Living memory (The Voz a Vos Bulletin, 2023)
This research investigates the nature (here understood as essential principles) of creative actions (art), taking as inspiration and reference the Colombian National Natural Park “Serranía de Chiribiquete” and the rupestrian paintings it houses from 20,000 years ago to the present day. This context is contrasted with that of the city of Bogotá and its contemporary artistic processes, in order to trace transversal elements, as well as differences, about art and life.It is clarified that this work does not intend to make an exhaustive analysis of the cosmovisions of the indigenous communities that inhabit the territory of Chiribiquete nor of the biological conditions of the ecosystem. For this purpose, reference will be made to works that have been devoted to it.Rather, this ongoing project seeks to approach what we might call "fundamental components of creative action (art)". This is with the intention of returning to a more sensitive and creative quality in "art" and in everyday life, in order to bring about a Living Life.So far, it has been possible to identify some essential principles of living action that make it manifest itself with greater or lesser pulsation. It has also been possible to identify differences between the context of Chiribiquete and Bogotá. These distinctions allow us to glimpse the respective dynamics of the relationship between the territory that contains a community and the practical cosmovision of the community that inhabits that territory. This, in turn, allows us to appreciate the presence or absence of notions that operate as cultural pillars.